Scaffolding teacher cognition: Changes in novice L2 teachers' pedagogical knowledge base through expert mentoring initiatives. (April 2017) - Karimi, Mohammad Nabi; Norouzi, Monireh
Abstract: Over the past two decades, there has been surge of interest in research on teacher cognition in L2 education. Although a variety of issues concerning teacher cognition have been investigated, this line of inquiry has not addressed the question of how L2 teachers' cognitive development can be supported. To address this gap, the present study aims to investigate how novice L2 teachers' pedagogical knowledge base might grow as a result of expert mentoring initiatives. To this end, four novice and four experienced teachers participated in the study. The four novice teachers received a mentoring program consisting of Video-Recorded Performance Analysis, Expert-Teacher Observation and Critical Friendship initiatives offered by the experienced teachers. Sample classroom performances of novice teachers before and after the mentoring program were video-recorded; the teachers were then interviewed regarding the thought units underlying their instructional moves using stimulated recall technique. Audio-recorded recollections of their performances were then transcribed and the underlying thought units were identified and categorized. Comparisons of the pedagogical thought units underlying their performance before and after the mentoring program revealed significant differences in both the total frequency with which they produced/expressed pedagogical thought units and the relative dominance of pedagogical thought categories.